The Influence of the Probing Prompting Model and Parental Attention on Improving Learning Outcomes of Madrasah Ibtidaiyah Students - Husna, Fina Atifatul; Karimah, Firdah Nailil (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2023)
The probing prompting model is still little used by teachers during the learning process, and parental attention is an activity that can support the student learning process and has a considerable impact, especially in terms of motivating student learning. The purpose of this study is to explain the effect of applying the probing prompting model and parental attention to improving learning outcomes. The sample in this study were students in grades IV A and IV B at the MINU Unggulan Wali Songo Sumuragung Sumberrejo Bojonegoro who were selected using a purposive sampling technique. The method used in this study is a quantitative research method with data collection techniques, namely, observation, questionnaires, tests, and documentation. The instrument used is a questionnaire and a test then analyzed using multiple regression analysis. Hypothesis testing shows that H0 is rejected and Ha is accepted, because the effect of the probing prompting model on improving learning outcomes is tcount (2.289) > t table (2.085) and the effect of parental attention on improving learning outcomes is t count (3.980) > thick t (2,085). Based on the results of the hypothesis, it can be concluded that there is an effect of applying the probing prompting model and parental attention to improving student learning outcomes at Madrasah Ibtidaiyah.